Anthesis and Silking Dynamics of Maize under Contrasting Nitrogen and Water Levels - Molla, Md. Samim Hossain; Nakasathien, Sutkhet; Sarobol, Ed; Vichukit, Vichan (Agriculture and Natural Resources, 2014)
Anthesis-silking and kernel setting may vary with the plant growth rate and environment. Two field experiments were conducted in December 2010 and January 2012 focusing on the short pre-anthesis and the prolonged bracketing-flowering stage drought (PBD), respectively, at the National Corn and Sorghum Research Center, Thailand. A split plot design with factorial randomized complete blocks was established with three replications, where two water regimes (well-watered and water-stressed) formed the main plots and two maize hybrids (Pioneer 30B80 and Suwan 4452) and three nitrogen levels (0, 160 (optimal) and 320 (supra-optimal) kg.ha-1 of N) collectively formed subplots. Under all conditions, relatively more biomass partitioning to the roots during the early vegetative stage might have lowered aerial growth and subsequently caused a slight delay in anthesis and silking in Pioneer 30B80. Albeit the plant and silk growth rates during the bracketing-flowering stage were higher in Pioneer 30B80 (even under combined stresses, which shortened the anthesis-silking period and interval (ASI) that caused more kernel setting than Suwan 4452), Pioneer 30B80 failed to complete 100% silking under PBD. Silking was more affected than anthesis by both stresses especially under PBD. Across the varieties, optimal nitrogen and water accelerated plant and silk growth, which also subsequently influenced timely flowering and shortened the ASI followed by more kernel setting.